2019
DOI: 10.1111/jar.12600
|View full text |Cite
|
Sign up to set email alerts
|

Domains of planning for future long‐term care of adults with intellectual and developmental disabilities: Parent and sibling perspectives

Abstract: BackgroundResearch shows that adults with intellectual and developmental disabilities (IDD) increasingly outlive caregivers, who often struggle to plan for the future and have little support and knowledge surrounding long‐term care planning.MethodsThe study team conducted interviews with parents and siblings of adults with IDD and performed qualitative coding using a modified grounded theory to explore domains of future planning and identify barriers and facilitators.ResultsThemes from the interviews revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
0
27
1
Order By: Relevance
“…Historically, future planning activities have been considered as a unified set, which families either do or do not engage in (DeBrine et al 2003). In their small-scale study using qualitative interviews of parents and siblings of brother-sisters within family homes, Lindahl et al (2019) found that respondents discussed housing, legal and financial planning, caregiving and guardianship, and medical or transportation needs. Considering our larger sibling sample, this study suggests that future planning involves three distinct domains: (1) legal, (2) residential options and (3) family discussions about the future planning for the brother-sister with a disability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, future planning activities have been considered as a unified set, which families either do or do not engage in (DeBrine et al 2003). In their small-scale study using qualitative interviews of parents and siblings of brother-sisters within family homes, Lindahl et al (2019) found that respondents discussed housing, legal and financial planning, caregiving and guardianship, and medical or transportation needs. Considering our larger sibling sample, this study suggests that future planning involves three distinct domains: (1) legal, (2) residential options and (3) family discussions about the future planning for the brother-sister with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…a non-legal document outlining desires for brothersister's future); contacting an attorney; establishing guardianship or power of attorney; creating a special needs trust; creating residential plans; and discussing the future with the family and brother-sister. Similar categories arose in qualitative interviews of parents and siblings (Lindahl et al 2019). Other considerations include the brother-sister's diagnosis, level of needed assistance and personal safety (Reed et al 2014), all of which may require families to opt for residences outside the family home or engage in financial and legal planning.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Despite their future roles, little research has focused on the perspectives of siblings of individuals with intellectual and developmental disabilities with respect to their engagement in future planning activities, barriers or correlates (see a review; Lee & Burke, 2020). In addition, most studies were conducted within European countries or the United States (Davys, Mitchell, & Haigh, 2016; Heller & Kramer, 2009; Lee, Burke, Arnold, & Owen, 2019; Lindahl et al., 2019; Taggart, Truesdale‐Kennedy, Ryan, & McConkey, 2012). Given the higher expectation of sibling caregiving in South Korea (Chon, 2018) and the potential impact of a different cultural background (e.g.…”
Section: Introductionmentioning
confidence: 99%